2007
DOI: 10.1091/mbc.e06-07-0635
|View full text |Cite
|
Sign up to set email alerts
|

The Assembly Pathway of the 19S Regulatory Particle of the Yeast 26S Proteasome

Abstract: The 26S proteasome consists of the 20S proteasome (core particle) and the 19S regulatory particle made of the base and lid substructures, and it is mainly localized in the nucleus in yeast. To examine how and where this huge enzyme complex is assembled, we performed biochemical and microscopic characterization of proteasomes produced in two lid mutants, rpn5-1 and rpn7-3, and a base mutant ⌬N rpn2, of the yeast Saccharomyces cerevisiae. We found that, although lid formation was abolished in rpn5-1 mutant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
125
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 47 publications
15
125
1
Order By: Relevance
“…At permissive temperatures, neither the Rpn2 nor the Rpt2 NLS deletion had severe impact on nuclear proteasome localization suggesting a redundancy of proteasomal NLSs ( Wendler et al , 2004). Isono et al (2007) later confirmed that Rpn2 provides a crucial NLS to aid nuclear import of the RP base and that the lid is separately imported. The nuclear import of the RP lid also requires importin α, though no classical NLS has been identified within RP lid subunits; rather Sts1, a short-lived protein that itself contains a classical NLS, associates with Rpn11 to facilitate nuclear import of the RP lid by importin αβ ( Chen et al , 2011).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 81%
“…At permissive temperatures, neither the Rpn2 nor the Rpt2 NLS deletion had severe impact on nuclear proteasome localization suggesting a redundancy of proteasomal NLSs ( Wendler et al , 2004). Isono et al (2007) later confirmed that Rpn2 provides a crucial NLS to aid nuclear import of the RP base and that the lid is separately imported. The nuclear import of the RP lid also requires importin α, though no classical NLS has been identified within RP lid subunits; rather Sts1, a short-lived protein that itself contains a classical NLS, associates with Rpn11 to facilitate nuclear import of the RP lid by importin αβ ( Chen et al , 2011).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 81%
“…1). We first investigated whether these methods could be applied to macromolecules in extracts from cells expressing chromosomally green fluorescent protein (GFP)-tagged proteasome subunit (Pre6) 14,21 , Hsp104, or ribosome subunit Rpl19a (Fig. 2) [31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…In the rpn2 mutant, the 26S proteasome was almost completely disassembled into the lid, base (lacking Rpn2) and CP even at the permissive temperature 21 . Indeed, the FCF curves of Pre6-GFP, Rpn1-GFP and Rpn7-GFP were dramatically altered ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations